Protective effect of aqueous garlic extract against oxidative organ damage in a rat model of thermal injury - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
Oxygen free radicals have been implicated in mediating various pathological processes including burn-induced organ damage. This study was designed to determine the possible protective effect of aqueous garlic extract against oxidative organ damage distant from the original burn wound. Under ether anaesthesia, rats were subjected to severe skin scald injury covering 30% of total body surface area. Rats were decapitated either 2 h or 24 h after burn injury. Aqueous garlic extract (1 ml/kg) was administered i.p. immediately after burn injury. In the 24-h burn group injection was repeated once more (at 12 hour) following the burn injury. Liver, intestine and lung tissues were taken for the determination of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and protein oxidation (PO). Burn injury caused a significant decrease in GSH level, and significant increases in MDA and PO levels, and MPO activity at post-burn 2 and 24 hours. Since garlic extract reversed these oxidant responses it seems likely that garlic extract protects tissues against oxidative damage. (C) 2003 Elsevier Science Inc. All rights reserved.
Keywords: burn; garlic; lipid peroxidation; glutathione; myeloperoxidase; protein oxidation; VASCULAR ENDOTHELIAL-CELLS; LIPID-PEROXIDATION; FREE-RADICALS; BURN INJURY; MELATONIN; GLUTATHIONE; LIVER; INFLAMMATION; MECHANISMS; ISCHEMIA